Research on the emission reduction effect of carbon emission trading policy supported by science and technology innovation - Xuefeng, Zhang; Yanqi, Cheng; Qingyang, Lv (Frontiers in Environmental Science, 2025)
Policy guidance and technological support are important driving forces for accelerating the process of carbon reduction and emission reduction, and the increase in carbon emissions in pilot provinces and municipalities has been reduced year by year since the implementation of the carbon emissions trading pilot in China. It is worth exploring what kind of influence science and technology innovation (STI) has played in this effectiveness. STI is both a macro policy and a micro economic activity. Panel data was collected for 30 provincial administrative units in China from 2008 to 2021, considering the carbon emissions trading pilot as a quasi-natural experiment. Starting from the positive impact of carbon emissions trading policy on emission reduction, we introduce the STI policy of national innovation demonstration zone and use the triple differences model to study the synergistic effect of the two policies. Further, continuous variables related to STI activities are substituted for STI policy, and a moderated test model is constructed to observe the impact of economic activities at different stages of STI on the effect of carbon trading policy. The conclusions of the study show that: (1) The policy of national innovation demonstration zones and the carbon trading policy can synergies with each other to promote emission reduction, and play the effect of 1 + 1>2, which is still robust after the parallel trend test and the individual placebo test; (2) The synergistic effect of the policy in the central and western regions is better than that in the eastern regions, and there is a large space for emission reduction in the future; (3) The positive effect of the carbon trading policy on emission reduction can be effectively amplified by STI activities. Enterprise scientific and technological capital investment, scientific and technological output, and technology marketization play an important role. China should steadily promote the policy of carbon emission right marketization, increase the support for STI activities, improve the incentive mechanism for scientific and technological talents, and continue to promote the marketization of scientific and technological achievements, so as to bring into play the greatest role of STI.